(untitled) (Bangladesh Journal of Urology, 2020)
Objective: This study was undertaken to find out the roles of dietary factors and physical activities in the formation of renal stones in our socio-demographic conditions. Methods: This cross-sectional analytical study was conducted among 70 patients from October 2011 to November 2012 in the department of SSMCMH and a few other private hospitals in Dhaka city. The study included all patients of either gender and all ages attending our out-patient department who were diagnosed to have renal stones. The dietary habits of the patients were explored by face to face interview using food frequency questionnaire (FFQ). The physical activities were evaluated by structured questionnaire, and the metabolic work-ups were done by urinalysis and blood analysis. The results were reviewed and analyzed with the help of SPSS 17. Result: Out of 70 patients about one-third were female (31.4%) and two-third were male (68.6%). Most of the study people belonged to age group 40-50 years. Mean was 43.7 years with standard deviation of 10.28 years. One-fifth of the respondents did minimal activities (0-5 hrs/day), One –third moderate activities (5-10 hrs/day) and about half severe activities (10-15hrs/day). One-fifth did not take any table salt but about one-fourth indulged much (>half tsf/day) and more than half took excessive (> 1tsf/day) salt. About 57.1% stone patients of the present study habitually have taken excessive salt, 24.3% patients took much salt and 18.6% used no added table salt. About one-third (37.71%) of the patients took calcium, one-fourth (25.71%) vitamin-D, one-fifth ascorbic acid and the rest had no supplementations. The patients having supplementations found to have more urinary levels of the corresponding supplements. More ingestion of green leafy vegetables and fruits and juices are associated with increased level of urinary oxalate. 24-hrs urinary oxalate level found to be associated with increased occurrence of renal stones. Most of the patients (64.3%) ingested habitually inadequate amount of fluid. Conclusion: The study showed some important observational facts in regard to the respondent’s diet and physical activities. The dietary and lifestyle modifications can reduce urinary stone disease. Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.23-27